Attracting Consumer Interest Through In-Store Live Streaming: Analysis Of Influence On Purchase Intention - Vanda Byar Sumekar Arum; Alldila Nadhira Ayu Setyaning (International Journal of Economics, Business and Innovation Research, 2024)
Live-streaming marketing via social media has attracted the attention of digital retail marketers in recent years. However, there is still a lack of evidence to understand the effect of in-store live-streaming on offline purchase intentions. This study aims to determine the effect of environmental stimuli on consumers' intention to purchase offline in-store after watching a live-streaming session in-store. The approach used in this study is a quantitative approach. The data collection technique was by distributing online questionnaires to 300 respondents using Google Form. The sampling technique used a non-probability sampling technique using the convenience sampling method which was then processed using structural equation modeling SEM (Structural Equation Modeling) using the PLS program. This study found that informativeness had a significant positive effect on consumers' attitude towards in-store influencers, attractiveness had a significant positive effect on consumers' attitude towards in-store influencers, wishful identification had a significant positive effect on consumers' attitude towards in-store influencers, parasocial interaction had a significant positive effect on consumers' attitude towards in-store influencers, and interactivity had a significant positive effect on consumers' attitude towards in-store influencers. In addition, consumers' attitude towards in-store influencers had a significant positive effect on purchase intention.